Merger and Acquisition Integration Model: A Practical Approach - Johan, Suwinto (JURNAL BISNIS STRATEGI, 2021)
This research aims to guide the merger and acquisition process for business practitioners in Asia. The research uses qualitative, descriptive analysis, and inductive approaches. This research is based on the samples of 20 transactions that have been performed in the last 25 years. The transactions involve companies from Indonesia, Malaysia, United States, United Kingdom, Japan, and Canada. The study proposes a merger and acquisition model with seven steps: determining the strategy, searching for the target, reviewing the target, confirmation and negotiation, transaction, and integrating into a business. The result of this study contributes to a new model of merger acquisition integration. The model will show the integration process in the financial services industry in South East Asia. The results support previous studies. The acquisition and integration model will assist the company's management in South East Asian countries to manage the merger integration process, especially in the financial industry. This research provides an integration model according to transactions in Asia in the financial service industry.